N-Acetyl-l-leucine improves functional recovery and attenuates cortical cell death and neuroinflammation after traumatic brain injury in mice - Nivedita Hegdekar (Nature Portfolio, 2021)
Abstract Traumatic brain injury (TBI) is a major cause of mortality and long-term disability around the world. Even mild to moderate TBI can lead to lifelong neurological impairment due to acute and progressive neurodegeneration and neuroinflammation induced by the injury. Thus, the discovery of novel treatments which can be used as early therapeutic interventions following TBI is essential to restrict neuronal cell death and neuroinflammation. We demonstrate that orally administered N-acetyl-l-leucine (NALL) significantly improved motor and cognitive outcomes in the injured mice, led to the attenuation of cell death, and reduced the expression of neuroinflammatory markers after controlled cortical impact (CCI) induced experimental TBI in mice. Our data indicate that partial restoration of autophagy flux mediated by NALL may account for the positive effect of treatment in the injured mouse brain. Taken together, our study indicates that treatment with NALL would be expected to improve neurological function after injury by restricting cortical cell death and neuroinflammation. Therefore, NALL is a promising novel, neuroprotective drug candidate for the treatment of TBI.